The Relationship Between Sedentary Behavior and Body Mass Index of Student from Faculty of Health Sciences Aisyiyah University Bandung During Online Learing - Sajodin Sajodin; llham Fadhil Muhamad; Sitti Syabariyah (Universitas Aisyah Pringsewu, 2022)
Sedentary behavior is behavior that is carried out in a sitting position or for long periods of time. The existence of the Covid-19 pandemic has an impact on lifestyle changes in the form of a decrease in physical activity caused by social disturbances and an increase in student eating patterns that occur in the incidence of obesity. The purpose of the study was to determine the relationship between sedentary behavior and the body mass index of students from the Faculty of Health Sciences, the University of Aisyiyah Bandung during the online learning period. The research method uses descriptive quantitative. Sampling using simple random sampling with a total of 246 respondents college students. The data collection technique used the Sedentary Behavior Questionnaire which was adapted by Rosenberg with a total of 18 statements and a scale of body mass index. The results showed that there was a relationship between sedentary behavior and body mass index with a correlation coefficient value (G) and p-value = 0.007 (p less than 0.05). so that the proposed hypothesis can be accepted. This shows that the higher a person is on sedentary behavior can affect obesity. The suggestion from this study is that students know how important it is to avoid sedentary behavior so that it does not have an impact on other health. Abstrak: Perilaku sedentari merupakan perilaku yang dilakukan dalam posisi duduk maupun berbaring dengan waktu lama. Adanya pandmi Covid-19 berdampak pada perubahan gaya hidup berupa penurunan aktivitas fisik yang diakibatkan karena adanya pembatasan sosial serta peningkatan pola makan mahasiswa yang berujung pada kejadian obesitas. Tujuan penelitian untuk mengetahui hubungan perilaku sedentari dengan indeks masa tubuh mahasiswa Fakultas Ilmu Kesehatan Universitas ‘Aisyiyah Bandung di masa pembelajaran daring. Metode penelitian menggunakan deskriptif kuantitatif. Pengambilan sampel menggunakan simple random sampling dengan jumlah 246 responden mahasiswa. Teknik pengumpulan data menggunakan Sedentary Behavior Questionnaire yang di adaptasi oleh Rosernberg dan dimodifikasi oleh Luthfiati dengan jumlah 18 pernyataan serta pengukuran indeks massa tubuh. Hasil penelitian menunjukkan bahwa terdapat hubungan perilaku sedentari dengan indeks massa tubuh dengan nilai koefisiensi korelasi (G) dan nilai p=0,007 (p kurang dari 0,05). Sehingga hipotesis yang diajukan dapat diterima. Hal ini menunjukan bahwa semakin tinggi perilaku sedentari seseorang dapat mempengaruhi tingginya resiko obesitas. Saran dari penelitian ini yaitu agar mahasiswa lebih mengetahui bagaimana pentingnya menghindari perilaku sedentari agar tidak berdampak terhadap kesehatan lainnya.